SENAM PROLANIS DAN PEMERIKSAAN KESEHATAN DASAR DI PUSKESMAS BOTANIA KOTA BATAM - Rizki Sari Utami Muchtar; Mira Agusthia (Awal Bros Journal of Community Development, 2020)
Kelurahan Belian which is covered by Puskesmas Botania has great potential to be able to become an independent village in terms of health, especially for the ederly. From thr community side, it has the ability to develop with strong support from the village apparatus. Organizing this community service activity aims to help the community, especially the elderly, to live healthy and maintain personal fitness. This is done by increasing the ability and self-conpidence to use the power they have. The community service methods used were prilanic exercise and basic health checks. The material provided includes the benefits of prolanis exercise, the benefits of basic health checks. The result obtained in this activity were that all participants stated that this activity was very useful because it increased the knowledge and fitness of the elderly.